Routing and schedule simulation of a biomass energy supply chain through SimPy simulation package. Issue 1 (27th July 2020) - Pinho, T.M.; Coelho, J.P.; Oliveira, P.M.; Oliveira, B.; Marques, A.; Rasinmäki, J.; Moreira, A.P.; Veiga, G.; Boaventura-Cunha, J.
Abstract : The optimisation of forest fuels supply chain involves several entities actors, and particularities. To successfully manage these supply chains, efficient tools must be devised with the ability to deal with stakeholders dynamic interactions and to optimize the supply chain performance as a whole while being stable and robust, even in the presence of uncertainties. This work proposes a framework to coordinate different planning levels and event-based models to manage the forest-based supply chain. In particular, with the new methodology, the resilience and flexibility of the biomass supply chain is increased through a closed-loop system based on the system forecasts provided by a discrete-event model. The developed event-based predictive model will be described in detail, explaining its link with the remaining elements. The implemented models and their links within the proposed framework are presented in a case study in Finland and results are shown to illustrate the advantage of the proposed architecture.